Institutional Intermediality: A Trifecta of Multi-Support Works from the Still Photography Division - Hardy-Vallée, Michel (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2024)
Among the institutions that supported photographers after WWII, the Still Photography Division (SPD) of the National Film Board of Canada (NFB) distinguished itself by its inherently intermedial approach. Originally established as a service provider for federal government departments, the Division quickly mutated during the 1960s into a protean institution that simultaneously functioned as image bank, photo laboratory, gallery, publisher, press agency, and multimedia project incubator. The books it published thus functioned alternatively as exhibition catalogues, coffee table books, souvenirs, diplomatic gifts, artists’ books, or photobooks.This paper seeks to understand the cultural ramifications of the kind of photographic work that was championed by the SPD from the late 1960s to the early 1970s by asking the question: Why promote a specific medium, photography, based on its intermedial uses?I address this paradox through the case study of three co-temporal photographic SPD books: Normand Grégoire’s (b. 1944) Série 4 (1971), Judith Eglington’s (b. 1945) Earth Visions (1973), and John Max’s (1936–2011) Open Passport (1973). All three were produced in a period during which the SPD’s mandate was pivotally redefined away from holding a mirror to Canada and towards fostering contemporary artists. Each of these works was also produced simultaneously for multiple supports—together, they span the domains of book, magazine, portfolio, exhibition, movie, and slide show—thus de-centering and de-hierarchizing media in a manner germane to art and media schools, as well as amateur practices. The works of Grégoire, Eglington, and Max thus point at a long-term narrative of resistance to the museal division of labour between media in the Canadian context and show how photobooks constitute a field to which scholars of the book should more actively contribute.